Marketing Strategy of Bielda Cake Through Facebook in Islamic Economis Persfective - Yuliaten; Abd. Malik; Nurlia Fusfita; Erwina Kartika Devi (Swakarya: Jurnal Penelitian Sosial dan Pengabdian Masyarakat, 2024)
The aim of this research is to find out the marketing mix strategy carried out by micro businesses at Bielda Cake and to find out the Islamic economic perspective on carrying out marketing strategies via Facebook media at Bielda Cake. This research uses qualitative methods, with data analysis techniques using descriptive analysis. Data collected through direct interviews with the owner of the Bielda Cake Shop and documentation. The author conducted research at the Bielda Cake Shop located in Betung Village, Kumpeh District, Muaro Jambi Regency. The results of this research can be seen that the Bielda Cake Shop markets its products using a form of marketing through an online system which includes social media Facebook. Apart from that, the Bielda Cake Shop also implements a marketing strategy by developing a marketing mix which consists of four elements, namely product, price, location and promotion. The products sold use quality and non-hazardous materials, prices are commensurate with quality, promotions use Facebook media and billboards, and strategic locations on the side of the road. The marketing strategy through Facebook media is in line with the marketing principles contained in Islamic economics, namely honesty without deception, maximum service and fairness without discriminating between consumers.